O6 Analyse this!: debrief on the psychiatric couch – dialogue with a deteriorating teacher. (5th November 2017) - Fernando, Asanga; Snelgrove, H
Abstract : In the focus on 'how-to-do-it' models, as opposed to craft – formulaic solutions to what constitutes good teaching in SBL have become rife. Following the example of military and aviation, but unlike other fields of learning and teaching, healthcare simulation has invested a lot of energy and time into the post simulation 'debrief'. Here facilitators are asked to encourage reflective practices proffer unpalatable truths, offer unvarnished advice or give people a pat on the back – depending on which 'transferable model' of debrief one cares to choose. Whole courses are dedicated to training clinical teachers in the simulation 'debrief' orthodoxy. National Quality Standards now list a number of such models that facilitators should be familiar with. One reason for this may be that the historical focus in 'simulation' on a discrete event – the clinical scenario and its concomitant debrief – has disinclined most clinical teachers to engage with components of a wider learning continuum; Drawing on multidisciplinary research from psychiatry, neuroscience and education, and the often clear disconnect evident in facilitating SBL debriefing, we will argue that successful learning is dependent on a compound of factors – among which rapport building, personal needs, shared goals, mental simulation, and follow up of longer term learning outcomes – and not simply reflective hindsight. In all of these the teacher has to develop confidence, to flourish professionally. We attempt to reconfigure the 'debrief' as a discrete moment on the learning continuum, more a professional conversation than a skill, where hopefully one gets a glimpse of compound effects of our teaching activities and can monitor learning for the future. Learning Objectives: To encourage reflection in to the different modalities of debriefing used in simulation and how these truly drive learning. To encourage a nuanced discussion about whether we can learn from other de-briefing arenas such as psychological trauma. Workshop Details: Maximum of 30 participants. Using presenters to engage participants.